Detection of Cyclists' Violation of Stop Sign Rules Using Smartphone Sensors - Tanaka, Shou; Takami, Kazumasa (TENCON ... IEEE Region Ten Conference, 2018)
In recent years, as the use of bicycles has become widespread, the number of bicycle-related accidents has been increasing. Major causes of bicycle accidents are the lack of knowledge of traffic rules on the part of bicycle users and the lack of opportunities for traffic safety education. This paper proposes a system that uses a smartphone attached to a bicycle to supplement safe bicycle ride education at home. As a basic study, the authors have developed a system that uses smartphone sensors to detect cyclists' violation of stop sign rules. The system makes the detection by combining data from the sensors in his/her smartphone and information about the locations of stop signs. This paper proposes to use the Google Street View Image API for collecting information about stop sign locations. A smartphone application for this system was developed and experiments in which subjects actually rode bicycles were conducted to examine the level of accuracy of detection of cyclists' violation of stop sign rules.